Application of Accentuated Eccentric Loading to Elicit Acute and Chronic Velocity and Power Improvements: A Narrative Review. (2022) - Merrigan, Justin J.; Borth, Jonathon; Taber, Christopher B; Suchomel, Timothy J; Jones, Margaret T
No abstract available